Integrating Sufi Spiritual Practices into Digital Detoxification Strategies: A Conceptual Framework for Mental Health in the Technological Age - Mamluatur Rahmah; Abdus Salam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This article examines the integration of Sufi spiritual practices into digital detoxification strategies as an alternative approach to improving mental health in the technological era. The increasing intensity of digital engagement, information overload, and constant online connectivity have contributed to psychological problems such as stress, anxiety, emotional exhaustion, and loss of meaning in life. In response to these challenges, Sufism offers a spiritual approach centered on self-awareness, inner purification, and emotional balance. This study employed a qualitative conceptual approach with library research methods. Data were collected from classical and contemporary literature on Sufism, digital detoxification, psychology, and mental health studies, including relevant journal articles, books, and scientific publications. Data were analyzed through thematic and interpretive analysis to identify the relevance of Sufi spiritual practices to contemporary digital-related mental health issues. The findings suggest that several Sufi practices, including muraqabah (self-awareness before God), muhasabah (self-reflection), and breath-based dhikr (remembrance of God), can contribute to reducing digital dependency, improving emotional formation, strengthening awareness, and restoring existential meaning. This study proposes a conceptual framework for integrating Sufi spirituality into a digital detoxification program by combining spiritual awareness with a psychological well-being approach. This study contributes to the development of an interdisciplinary discourse connecting Sufism, mental health studies, and digital culture, while also offering an alternative spiritual-based model for addressing psychological challenges in the digital age.